2004
DOI: 10.1590/s1415-47572004000400005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of codon 72 P53 polymorphism in Brazilian women with cervix cancer

Abstract: The p53 codon 72 polymorphism seems to be associated with HPV-carcinogenesis, although controversial data have been reported. A series of Brazilian women with cervix carcinomas were analyzed. Ninety-nine (67%) of 148 women were found to be homozygous (arg/arg) for the arginine polymorphism, and 49 (33%) were heterozygous (arg/pro). This polymorphism may be an important determinant of the risk for cervix cancer, but does not seem to be sufficient for carcinogenesis. Key words: p53 polymorphism, codon 72, geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Although, no significant difference was demonstrated for the genetic and genotypic frequencies in the two groups, a higher frequency was observed for the p53Arg allele in both groups. Similar frequency patterns have been observed for different tumors (Bonafé et al, 2003;Brenna et al, 2004;Cortezzi et al, 2004;Lima et al, 2006). Our study supports the evidence that p53Arg is the most common allele in Latin American populations (Gallo et al, 2005).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Although, no significant difference was demonstrated for the genetic and genotypic frequencies in the two groups, a higher frequency was observed for the p53Arg allele in both groups. Similar frequency patterns have been observed for different tumors (Bonafé et al, 2003;Brenna et al, 2004;Cortezzi et al, 2004;Lima et al, 2006). Our study supports the evidence that p53Arg is the most common allele in Latin American populations (Gallo et al, 2005).…”
Section: Resultssupporting
confidence: 79%
“…Our study supports the evidence that p53Arg is the most common allele in Latin American populations (Gallo et al, 2005). However, worldwide literature data on genetic and genotypic frequencies are conflicting, due to ethnic differences among the populations studied (Brenna et al, 2004;Siddique et al, 2005). Different confounding factors should be considered as well, including sample size, the source of DNA, the detection methods, and the inter-laboratory variations in the protocols affecting the ability to detect TP53 polymorphisms (Brenna et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…However reported data on the prevalence of p53 polymorphism in cervical cancer patients are controversial and the ethnic group characteristics seem to be an important reason for discrepancies in the frequency of this polymorphism (Brenna, 2004;Wang, 1999;Wu, 2004;Pegoraro, 2002;Klug, 2001;Szarka, 2000;Agorastos, 2000;Hildesheim, 1998;Bhattacharya, 2002). Moreover, other potential confounding factors should be also considered including the sample size, the source of DNA and the detection techniques used.…”
Section: Topics On Cervical Cancer With An Advocacy For Prevention 200mentioning
confidence: 99%
“…Moreover, other potential confounding factors should be also considered including the sample size, the source of DNA and the detection techniques used. Another important reason for these discrepant results could be misclassification of the p53 polymorphism, due to inter-laboratory variations in protocols, affecting the ability to detect p53 polymorphisms (Brenna, 2004;Govan, 2007;Sousa, 2007).…”
Section: Topics On Cervical Cancer With An Advocacy For Prevention 200mentioning
confidence: 99%
“…These findings are statistically significant suggesting that type of NMSC determine where the malignant lesion will develop; either in directly sun-exposed area or the opposite. Moreover, Brenna et al concluded that the controversial data found by the different studies have been attributed to ethnic differences, but other potential confounding factors should be considered, including the sample size, the source of DNA, and the detection techniques use (52).…”
Section: B Amentioning
confidence: 99%